OPTIMALISASI PERAN BANK SAMPAH DALAM PEMBERDAYAAN MASYARAKAT DESA TANJUNG GADING - Rahmah, Nur (Jurnal GeoCivic, 2024)
Waste banks are an innovation in community-based waste management which aims to reduce the volume of waste and improve community welfare. This research aims to examine optimizing the role of waste banks in empowering communities in Tanjung Gading Village. The method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the waste bank in Tanjung Gading Village not only functions as a place for collecting and processing waste, but also as a means of environmental education and economic empowerment for the local community. Through waste banks, people are trained to sort waste and manage it into products that have sales value. Apart from that, this activity also succeeded in increasing environmental awareness and solidarity between residents. However, optimizing the role of waste banks still faces several obstacles such as limited facilities and lack of active participation from all levels of society. To overcome these obstacles, closer cooperation is needed between village governments, communities and the private sector. Thus, the waste bank can be an effective instrument in improving the welfare and quality of life of the people of Tanjung Gading Village.